ANALYSIS OF POWER PLANT MICROHYDRO (PLTMH) ON RIVER FLOWS ON MONGONDOW RIVER IN MUNTOI VILLAGE REGENCY OF BOLAANG MONGONDOW - Parabelem T.D. Rompas (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2011)
The microhydro power plant (PLTMH) has been analyzed. The objectives of the research are to get water power capasity of PLTMH and electric energy in a year. The data was collected by direct observation in the field. It’s found that water power capasity of PLTMH and electric energy in a year are 19.5 kW and 170.829 MWh.